Telaah Epistemologis atas Praktik Manajemen Pendidikan Islam di Lembaga Madrasah Aliyah - Wahidah, Romlatul; Solichin, Mohammad Muchlis (Kartika: Jurnal Studi Keislaman, 2025)
This article explores the epistemological values embedded in the management of Islamic education at MA As-Salafiyah Sumber Duko Pakong Pamekasan. Using a qualitative descriptive approach with a case study method, the research aims to describe and analyze how values rooted in Islamic epistemology such as tawhid (oneness of God), amanah (trustworthiness), shura (consultation), and ihsan (excellence) are implemented in the managerial practices of the institution. Data were obtained through direct observation, in-depth interviews with key informants, and documentation analysis. The data were then analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings show that these values are integrated holistically into the planning, organizing, actuating, and controlling processes. Tawhid fosters a sense of spiritual responsibility in leadership, amanah ensures integrity in financial and administrative management, shura strengthens participatory decision-making, while ihsan enhances the commitment to educational quality and service.